2021
DOI: 10.1002/ijc.33579
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of primary and metastatic breast and pancreatic tumors upon intravenous delivery of a PRDM14‐specific chimeric siRNA/nanocarrier complex

Abstract: PRDM14 is highly expressed in several cancers but is not detected in normal tissues.It confers cancer stem cell-like properties, including chemoresistance and distant metastasis, to cancer cells. Herein, we aimed to develop a highly effective therapy against advanced stage cancer based on intravenously delivered PRDM14-targeted siRNA. First, we examined PRDM14 expression and gene amplification in breast and pancreatic tumors and cell lines. PRDM14 was expressed in breast cancer, including the triple-negative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…PEG-PLL or PEG-PLO also met this condition, and PRDM14 uPIC demonstrates antitumor effects. 12 , 46 ) A higher number of PEG-PLL molecules is required, compared with PEG-PLO molecules, to carry one molecule of siRNA; therefore, a complex of siRNA with PEG-PLL causes adverse effects, and is expensive to use for treatment, compared with PEG-PLO. A complex of siRNA with PEG-PLO as DDS has been selected and a phase I clinical trial started.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…PEG-PLL or PEG-PLO also met this condition, and PRDM14 uPIC demonstrates antitumor effects. 12 , 46 ) A higher number of PEG-PLL molecules is required, compared with PEG-PLO molecules, to carry one molecule of siRNA; therefore, a complex of siRNA with PEG-PLL causes adverse effects, and is expensive to use for treatment, compared with PEG-PLO. A complex of siRNA with PEG-PLO as DDS has been selected and a phase I clinical trial started.…”
Section: Discussionmentioning
confidence: 99%
“…siRNAs must penetrate target cell membranes and escape from endosomes. We reported that the use of calcium phosphate (CaP) hybrid micelles, 44 ) polyethylene glycol (PEG)–poly-l-lysine (PLL) block copolymers, 45 ) and branched PEGylated poly-l-ornithine (PLO) 46 ) because DDSs for siRNA may overcome several difficulties encountered by conventional systemic delivery systems. The complex composed of these carriers with siRNA accumulates in solid tumors through enhanced permeability and retention effects because of their small particle size.…”
Section: Oligonucleotide Therapeutics Targeting Prdm14mentioning
confidence: 99%
See 3 more Smart Citations